A Retrospective Study of Patient-Reported Data of Bullous Pemphigoid and Mucous Membrane Pemphigoid From a US-Based Registry - Lee, Janet; Seiffert-Sinha, Kristina; Attwood, Kristopher; Sinha, Animesh A. (Frontiers in Immunology, 2019)
Bullous pemphigoid (BP) and mucous membrane pemphigoid (MMP) are rare chronic autoimmune disorders characterized by subepidermal blistering. For the United States, there is a limited amount of studies in BP and MMP that address disease demographics and clinical data.. In order to more comprehensively examine disease demographics and clinical factors, we performed a retrospective analysis of patient-reported data of 138 BP and 165 MMP patients enrolled in the International Pemphigus & Pemphigoid Foundation (IPPF) disease registry from 2010-2016. Patient-reported data was compared to a local biorepository compiled by our group. We confirm a female predominance in BP (M:F ratio 1:2.1) and MMP (M:F ratio 1:4.3), and a late onset within the 6th decade of life (average age at diagnosis, 59.1 ± 17.5 years for BP and 54.8 ± 11.2 years for MMP). MMP patients had a significantly longer delay in diagnosis >12 months than BP patients (38% vs. 21%, respectively, p=0.002). Similar to other autoimmune conditions, a large number of BP (34%) and MMP (35%) patients present with other co-existing autoimmune disorders, with the most common being thyroid disease for both groups. Increased illness activity was paralleled by an increase in severe limitations of daily activities. The vast majority of patients received high intensity immunosuppression for both BP (49%) and MMP (49%) groups. The majority of BP patients reported therapy with prednisone combined with other immunosuppressants (40%), and the majority of MMP patients received immunosuppressants other than prednisone (55%). The clinical and demographic findings from both the national and local datasets (with 19 BP and 43 MMP patients) were largely consistent with each other, and support those reported in other countries.